Biochemical study of human articular cartilage and meniscus on aging and joint disease (author's transl) - Shindo, H; Karube, S; Masuda, M; Hayashi, Y; Igarashi, M (Nippon Seikeigekagakkai zasshi, 1981)
We studied biochemically the changes associated with aging and disease in the collagen of articular cartilages and menisci. Pepsin soluble and insoluble collagen were obtained by the method of Miller (1971) from the articular cartilages of seven healthy young and adult, six healthy aged subjects, and of six osteoarthritic and six rheumatoid arthritic patients. One portion of pathological cartilage was histologically examined to eliminate any possible contamination of the fibrous tissue and subchondral bone, and to classify the pathological findings. By the method of Miller, the pepsin soluble and insoluble collagen were also obtained from four adult and six aged menisci. Amino acid composition and carbohydrate contents were studied in insoluble collagen. The type of soluble collagen were analyzed with SDS disc electrophoresis. The amount of crosslinks in insoluble collagen was analyzed by the method of Masuda (1976) using automatic amino acid analyzer. The results obtained where shown as follow: 1) Solubility of collagen by pepsin decreased with aging on articular cartilages and menisci. In osteoarthritis and rheumatoid arthritis, the solubility of collagen by pepsin was different between the samples, and generally higher than that of collagen from the aged articular cartilages. 2) In respect to aldimine crosslinks of insoluble collagen, the dihydroxylysinonorleucine (DHLNL), hydroxylysinonorleucine (HLNL) and lysinonorleucine (LNL) increased with aging. DHLNL and HLNL were present in the nonreduced collagen in vitro. It was shown that the aldimine crosslinks had been already reduced in vivo. 3) The contents of carbohydrate of insoluble collagen from articular cartilage showed lower values than that of type II collagen as described previously. The hexosamine contents increased and those of uronic acid and hexose decreased with aging. In osteoarthritic and rheumatoid arthritic articular cartilages, the contents of uronic acid were lower than that of healthy aged group. The carbohydrate contents of menisci were similar to that of type I collagen. 4) concerning the type of collagen, healthy articular cartilages consisted of type II collagen. In collagen of aged cartilages and those of fibrillated and osteophytic cartilages in osteoarthritic and rheumatoid arthritic patients, the type II collagen were mixed with type I collagen ranging from 13.8% to 64.5%, although the analysis of articular cartilages in this study showed histological characteristics of hyaline cartilage. The type of soluble collagen in adult and aged menisci were composed of type I collagen in spite of aging.